Effective multicast programming in large scale distributed systems - Eugster, Patrick Th; Boichat, Romain; Guerraoui, Rachid; Sventek, Joe (Concurrency and computation, 2001)
Many distributed applications have a strong requirement for efficient dissemination of large amounts of information to widely spread consumers in large networks. These include applications in e‐commerce and telecommunication. Publish/subscribe is considered one of the most important interaction styles with which to model communication on a large scale. Producers publish information on a topic and consumers subscribe to the topics they wish to be informed of. The decoupling of producers and consumers in time, space, and flow makes the publish/subscribe paradigm very attractive for large scale distribution, especially in environments like the Internet. This paper describes the architecture and implementation of DACE (Distributed Asynchronous Computing Environment), a framework for publish/subscribe communication based on an object‐oriented programming ion in the form of Distributed Asynchronous Collection (DAC). DACs capture the variants of publish/subscribe, without blurring their respective advantages. The architecture we present is tolerant of network partitions and crash failures. The underlying model is based on the notion of Topic Membership: a weak membership for the parties involved in a topic. We present how Topic Membership enables the realization of a robust and efficient reliable multicast on a large scale. The protocol ensures that, inside a topic, even a subscriber who is temporarily partitioned away eventually receives a published message. Copyright © 2001 John Wiley & Sons, Ltd.